BIODIVERSITY OF HYDROCARBON-PRODUCING MICROALGAE FROM OIL CONTAMINATED IN COASTAL ZONE OF BATAM ISLAND - Susilaningsih, Dwi; Siburian, Marlinang Diarta; Murniasih, Tutik (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
Addressing to the environmental and energy crises in Indonesia, the new alternative of green-economic-energy sources is required. In this study marine microalgae were isolated from oil-polluted coastal zone in Batam Island for alternative energy sources. The research was carried out by collecting the sea water samples from several peninsulas of Batam Island. The abundance of microalgal diversity was observed. The isolation was done by capillary micropipette technique. The method of specific screening for hydrocarbon-producing microalgae was done using selected media, CO2 rate and light intensity period treatments. The results showed that the Cyanobacteria and diatom occupied the Batams coastal waters. From the isolated samples, 11 strains positively deposit the hydrocarbon in their cells. Further study for determining the isolates and their properties is still in progress.